ADVANCING NATION FOOD SUPPLY THROUGH ACCELERATOR-DRIVEN TECHNOLOGY FOR CONTROLLED ENVIRONMENT AGRICULTURE - Pamungkas, Lukas Sangka; Widjaja, Anton Wachidin (President University, 2024)
In this disruption era, ventures must foster the transition of their digital transformation. Digital transformation can be obtained by the entry of the accelerator into the process. Siemens – Advanced Manufacturing Transformation Centre (AMTC) is one of the enterprises in which ventures can move their business operations to a different level, emphasizing vertical and horizontal integration. The AMTC provides investment projects with systematic training programs, the service of consultants, and the industry 4.0 environment. Through involvement in these organizations and utilizing the sandbox environment, ventures can upgrade their talents, expertise, and capacities to accept digital transformation and rope innovation throughout the business segment. It could enable firms to patent the technology and explore new concepts, apart from developing ingenious solutions and driving business development. In their operation, Siemens AMTC has a Digital Enterprise Experience Center (DEX). The client gets to see how the real and digital worlds enable one to design and facilitate a realization of the value chain as an end-to-end process optimized by a perpetuating data flow using DEX. It is important here to state that a real Digital Enterprise must be capable of utilizing the virtually infinite amount of information available to make the right decisions quickly and without doubt as well as deliver top-notch goods through the implementation of lean manufacturing. Not only provide access to industry experts, AMTC also connect the client to hands-on training (transition), access to advance technology training facility, also access to advance manufacturing equipment. There is constant pressure from the global shifts that influence the industrial world such as changes in geo-political climate, technology, markets, and climatic change. The key strategies, therefore, come into play to address such challenges include digitalization and automation. The Digital enterprise is doing exactly this by overcoming the physical space between the real and the digital world. So, with the synchronization of the real world and the digital world, the integration of the design to realization is enabled on one hand, and the constant flow of data is a means of optimization on the other. This is happening in the Artisan Green activity, using the digital twin, they can create uncertainty in their product harvest to become more certainty. Artisan Green successfully implementing Controlled Environment Agriculture (CEA) and working in cooperation with Siemens. The collaboration basic idea is to improve hydroponic operations by connecting an improved Farm Management System via Siemens’ technologies to create parameter for another rack adoption based on the problem that solved by the integrated system. This system represents some principles of CEA, as for example the control of environment and the rational use of resources. This partnership brought a very crucial agriculture revolution in Singapore as a nation with no land for Agriculture yet lacks some essential foods. It aims to achieve the next level of hi-tech, environmentally friendly hydroponic farming and tripling the production rates of energy, yield, and recycling. Modern techniques of farming are under pressure from factors that include population growth and the rise of demand for fresh and healthy food, climate change and fluctuations as well as scarcity of land for farming. Consequently, Singapore has embarked on an aggressive strategy to upgrade the capacity of this sector to supply at least 30 per cent of the country’s nutritional requirements organically by the year 2030. This goal is also part of the Singapore Green Plan 2030 as a plan for developing resilience of the food system in Singapore. The S30 million grant named “30 by 30 Express” shows the government’s commitment for local food production thus creating favorable conditions for businesses such as Artisan Green. By using this Siemens’ modern technology and experience in automation and digitalization, Artisan Green will have its indoor farms include a modern integrated farm management system, which will increase the utilization of inputs, decreasing a negative impact on the environment. The centralized and vertical farming system implemented at Artisan Green ensures that land is used to optimum potential and thus increases the productivity of the farms thereby also cutting on the use of pesticides and herbicides. This paper explains will explain more about the objectives of digital transformation, the process model, the difficulties, and finally the phase beyond disruption. It concluded that an accelerator could offer co-creation, collaboration, and networking to gain bigger market scalability opportunities for ventures, supported by cutting-edge infrastructure and technology, a sandbox for digital transformation, also skill development/ certification.